Predictors of symptomatic hyperviscosity in Waldenström macroglobulinemia. Issue 11 (2nd October 2018) - Abeykoon, Jithma P.; Zanwar, Saurabh; Ansell, Stephen M.; Winters, Jeffrey; Gertz, Morie A.; King, Rebecca L.; Murray, David; Habermann, Thomas; Dingli, David; Muchtar, Eli; Go, Ronald S.; Leung, Nelson; et al.
Abstract: Symptomatic hyperviscosity is a well‐established phenomenon in Waldenström macroglobulinemia (WM). Monoclonal IgM can variably impact intrinsic serum viscosity, leading to widely disparate symptomatic thresholds for development of hyperviscosity‐related symptoms. Data regarding the predictors of symptomatic hyperviscosity and outcomes related to this complication remain scarce and a recent study proposed that IgM >6000 mg/dL be considered a new criterion for initiating therapy in otherwise asymptomatic (smoldering) WM to pre‐empt hyperviscosity‐related injury. Herein, we attempt to identify predictors of the development of symptomatic hyperviscosity and its impact in patients with WM. Of 997 WM patients evaluated from January, 1996 through June, 2017, symptomatic hyperviscosity was observed in 130 (13%) patients. Overall survival (OS) of these 130 patients was similar to that of patients without symptomatic hyperviscosity (median: 11.5 vs 11.6 years; P  = 0.63). On multivariate‐analysis, only viscosity >1.8 cp (risk ratio: 4.0, P  = 0.02) assessed at the time of WM diagnosis was an independent predictor for the development of subsequent symptomatic hyperviscosity. Among patients with smoldering WM and IgM >6000 mg/dL at diagnosis ( n  = 13) who were managed expectantly, the median time‐to‐initial therapy was 6.9 years and only 15% developed hyperviscosity‐related symptoms subsequently. In summary, the occurrence of symptomatic hyperviscosity does not impact OS. Serum viscosity at diagnosis of WM, and not IgM concentration, represents the single most important independent predictor for development of subsequent hyperviscosity‐related symptoms. Patients with smoldering WM and high serum IgM can be safely observed in the absence of any indications per the Consensus recommendations to initiate WM‐directed therapy.